1986
DOI: 10.1063/1.336527
|View full text |Cite
|
Sign up to set email alerts
|

Numerical calculation of the temperature distribution and evolution of the field-ion emitter under pulsed and continuous-wave laser irradiation

Abstract: Articles you may be interested inQuantum-dot laser with a metal-coated waveguide under continuous-wave operation at room temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Numerous authors have constructed one-dimensional models to determine the time-varying temperature profile of the specimen tip when it is irradiated with a pulsed laser Cerezo & Smith, 1987;Liu et al, 1986;Seidman & Scanlan, 1971;Vurpillot et al, 2006!. An underlying assumption of these models is that the temperature equilibrates across the specimen very rapidly and subsequently only varies along the axial direction, even when the specimen is illuminated from the side.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous authors have constructed one-dimensional models to determine the time-varying temperature profile of the specimen tip when it is irradiated with a pulsed laser Cerezo & Smith, 1987;Liu et al, 1986;Seidman & Scanlan, 1971;Vurpillot et al, 2006!. An underlying assumption of these models is that the temperature equilibrates across the specimen very rapidly and subsequently only varies along the axial direction, even when the specimen is illuminated from the side.…”
Section: Discussionmentioning
confidence: 99%
“…However, the apparent carbon concentrations are nearly 25 at% without any correction for detection loss in the pulsed laser atom probe, indicating that very little detection loss occurs. The tip surface temperature at the time of field evaporation is sufficiently high by pulse laser irradiation (Liu et al, 1986; Marquis & Gault, 2008), which significantly reduces detection loss. The number of carbon atoms composed of molecular ions increases at high temperatures.…”
Section: Carbon Analysis Of θ-Fe3cmentioning
confidence: 99%
“…irradiation (Liu et al, 1986;Marquis & Gault, 2008), which significantly reduces detection loss. The number of carbon atoms composed of molecular ions increases at high temperatures.…”
Section: Pulsed Laser Atom Probementioning
confidence: 99%
“…The tip was then illuminated with the 1064 nm beam and the beam placement was verified using an infrared viewer. It has been shown that FIM tips heated by a continuous wave laser reach the final temperature on µs time scales [40]. Because the tip was not incandescent during heating, the optical pyrometer could not be used to determine the tip temperature.…”
Section: Experimental Procedures For Diffusion Studiesmentioning
confidence: 99%